Comparative characteristics of the home care nursing services used by community‐dwelling older people from urban and rural environments. (5th August 2012) - Borowiak, Ewa; Kostka, Tomasz
Abstract Aim To compare home care nursing services use by community‐dwelling older people from urban and rural environments in Poland. Background In the current literature, there is a lack of data based on multidimensional geriatric assessment concerning the provision of care delivered by nurses for older people from urban and rural environments. Design Cross‐sectional random survey. Method Between 2006–2010, a random sample of 935 older people (over 65 years of age) from an urban environment and 812 from a neighbouring rural environment were interviewed in a cross‐sectional survey. Findings The rural dwellers (82·8%) nominated their family members as care providers more often than the city inhabitants (51·2%). Home nursing care was provided to 4·1% of people in the city and 6·5% in the county. Poststroke condition, poor nutritional status, and low physical activity level, as well as low scores for activities of daily living, instrumental activities of daily living, and Mini‐Mental State Examination values, were all determinants of nursing care, both in urban and rural areas. In the urban environment, additional predictors of nursing care use were age, presence of ischaemic heart disease, diabetes and respiratory disorders, number of medications taken, and a high depression score. Conclusions Poor functional status is the most important determinant of nursing care use in both environments. In the urban environment, a considerable proportion of community‐dwelling elders live alone. In the rural environment, older people usually have someone available for potential care services. The main problem seems to be seeking nursing care only in advanced deterioration of functional status.